The Phenomenon of Fear of Missing Out (FOMO) in the Formation of a Healthy Lifestyle and Social Identity of Golerun Running Club Members - Lia Amalia Supandi; Khaerudin Imawan; Leni Rohida (Syntax Corporation Indonesia, 2026)
This study aims to analyze the role of FOMO in the running community, describe the process of forming social identity through membership, interaction, and shared activities, and interpret its relevance in influencing the way members interpret their involvement, both as an effort to maintain health and as a need for social recognition and existence. The study used a descriptive qualitative method with in-depth interview techniques with six informants, participatory observation, and documentation. The results of the study show that there is a shift in the meaning of FOMO to